Looking for Evidence of Public Health's Role for Long-Term Evacuees - Clow, Barbara; Haworth-Brockman, Margaret; Boily-Larouche, Geneviève; Qadar, Zeeshan; Keynan, Yoav (Frontiers in Public Health, 2019)
Many Canadians have had personal experience of a major emergency or disaster at some point in their lifetime and close to a third of those affected were evacuated from their homes or communities. Most evacuations have lasted less than 2 weeks, but in some instances, people have been displaced for months or years. For example, hundreds of residents evacuated following flooding in Lake St. Martin, Manitoba in 2011, remain displaced today. In order to learn more about the roles and responses of public health for long-term evacuees (LTEs) in Canada, we conducted a narrative review of published English-language documents, beginning with literature specific to Canada and then expanding to include literature on other high-income countries. We found that while researchers have explored public health considerations in emergency preparedness, acute disaster management, and resettlement in these contexts there is a dearth of published evidence regarding the public health implications of prolonged evacuation and the public health responses to long-term evacuation in Canada and in other high-income countries. Because the public health needs of diverse populations of LTEs have not been fully investigated, it is likely that they are neither well-understood nor adequately addressed in public health policy and practice.